2020
DOI: 10.1097/md.0000000000022728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of positive dispatcher encouragement on the maintenance of bystander cardiopulmonary resuscitation quality

Abstract: Background : Implementation of dispatcher-assisted cardiopulmonary resuscitation (DACPR) has increased the likelihood of bystander CPR upon cardiac arrest. However, the quality of CPR has been found to be very low. In this study, we aimed to compare CPR quality between the current DACPR practices and the interventional instruction of adding verbal encouragement from the dispatcher. Methods : In this randomized controlled trial, we recruited adult (age ≥18) laypersons wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
2
0
4
Order By: Relevance
“…Numerous techniques have been implemented in DA-CPR protocols to increase chest compression depth, such as using verbal motivation by the dispatcher or real-time feedback strategies. 15,34,35 This study also demonstrated that non-health care provider participants who received CPR instruction and health care provider participants who received no CPR instruction had equal CPR performance and quality. This result suggests that providing frequent CPR education or training to lay rescuers would improve the quality of bystander CPR through an effective DA-CPR protocol, leading to improvements in the outcomes for patients with sudden cardiac arrest.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Numerous techniques have been implemented in DA-CPR protocols to increase chest compression depth, such as using verbal motivation by the dispatcher or real-time feedback strategies. 15,34,35 This study also demonstrated that non-health care provider participants who received CPR instruction and health care provider participants who received no CPR instruction had equal CPR performance and quality. This result suggests that providing frequent CPR education or training to lay rescuers would improve the quality of bystander CPR through an effective DA-CPR protocol, leading to improvements in the outcomes for patients with sudden cardiac arrest.…”
Section: Discussionsupporting
confidence: 52%
“…According to the standardized DA-CPR program, instruction was provided to participants using the speakerphone function. After the participants were instructed regarding proper posture, hand placement, compression rate, and compression depth, the dispatcher activated a metronome set to 110 beats per minute 15 using Metronome Online (EMusic Institute Corporation; Valencia, California USA). The dispatcher was blinded in another isolated room and communicated with the participants only using the provided mobile phones.…”
Section: Study Protocolmentioning
confidence: 99%
“…Intervenções comunitárias e programas de treinamento comunitário aumentaram a realização de RCP por leigos, embora não tenham aumentado significativamente a sobrevida 37,44 . Modificações nas instruções da RCP assistida por telerregulador, enfatizando o método hands-only, melhoraram a qualidade das compressões e reduziram o tempo até o início do procedimento 18,25 .…”
Section: Resultsunclassified
“…A RCP por leigos permanece como uma das principais maneiras de aumentar a sobrevida na PCR fora do ambiente hospitalar [7][8][9][10][11][12][13][14][15][16][17][18][19] . Verifica-se que várias técnicas e ferramentas estão disponíveis para auxiliar os leigos na realização de uma RCP de qualidade, aqui descritas de acordo com o tipo de intervenção proposta nos respectivos artigos.…”
Section: Discussionunclassified
“…Regarding training, mass public CPR campaigns may not be cost-effective for many LMICs, however tCPR may present to be a cost-effective alternative. Recent studies have shown that continuous telephonic encouragement and coaching by a call-taker or dispatcher over the phone may result in improved compression rates [33] , depth and overall CPR quality [34] . Considering this, it would be important to include continuous coaching in the training and implementation of OHCA telephonic recognition and tCPR guidelines.…”
Section: Discussionmentioning
confidence: 99%